The Effect of HIV/AIDS Infection on the Clinical Outcomes of COVID-19: A Meta-Analysis - Yousef Moradi; Marzieh Soheili; Hojat Dehghanbanadaki; Ghobad Moradi; Farhad Moradpour; Seyede Maryam Mahdavi Mortazavi; Hamed Gilzad Kohan; Mostafa Zareie (Frontiers Media S.A., 2022)
Purpose: Patients with HIV may be more likely to become severely ill from COVID-19. The present meta-analysis aims to determine the impact of HIV/AIDS infection on the clinical outcomes of COVID-19. Methods: A comprehensive literature search was performed to identify relevant cohort studies to evaluate the association of HIV/AIDS infection with clinical outcomes of COVID-19. International databases, including PubMed (Medline), Web of Sciences, Scopus, and Embase, were searched from the emergence of the COVID-19 pandemic until January 2022. We utilized the risk ratio (RR) with its 95% confidence interval (95% CI) to quantify the effect of cohort studies. Results: Twelve cohort studies were included in this meta-analysis, which examined a total number of 17,786,384 patients. Among them, 40,386 were identified to be HIV positive, and 17,745,998 were HIV negative. The pooled analyses showed HIV positive patients who were co-infected with SARS-CoV-2 were 58% more likely to develop a fever (RR=1.58; 95% CI: 1.42, 1.75), 24% more likely to have dyspnea (RR=1.24; 95% CI: 1.08, 1.41), 45% more likely to be admitted to ICU (RR=1.45; 95% CI: 1.26, 1.67), and 37% more likely to die from to COVID-19 (RR=1.37; 95% CI: 1.30, 1.45) than HIV negative patients. Conclusion: HIV/AIDS coinfection with COVID 19 increased the risk of fever, dyspnea, ICU admission, and mortality.